A Rare Case Presentation of Vitiligo Associated With Atezolizumab - Kemnasom Nwanwene MD; Mahmoud Abdallah MD; Toni Pacioles MD (SAGE Publishing, 2023)
Immune checkpoint inhibitors (ICIs) are monoclonal antibodies used in the treatment of solid and hematologic malignancies. Immune checkpoint inhibitors target the T-cell deactivation system via the cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) receptor, programmed cell death protein 1 (PD-1) receptor, and programmed cell death ligand 1 (PD-L1). As a result, the activated T-cell enhances the host tumor response. However, even with their essential clinical benefits, ICIs are associated with a broad spectrum of adverse effects that can be generalized or tissue-specific inflammatory responses known as immune-related adverse events (irAEs). The most common dermatologic toxicity manifests mainly as maculopapular rash and pruritus. Understanding the complexity of immune-mediated response and the importance of clinical histopathologic correlation in recognizing irAEs allows for appropriate intervention and patient care due. We present the case of a 71-year-old African American male diagnosed with a large-cell poorly differentiated neuroendocrine tumor in the gastroesophageal junction of the stomach with mediastinal lymphadenopathy. He was treated with carboplatin, etoposide, and atezolizumab for 4 cycles. However, he developed vitiligo while on maintenance atezolizumab, which is rarely seen with atezolizumab use. Despite the improving clinical outcomes in oncology with ICIs, their adverse effects should not be ignored. When promptly recognized and treated, patients on ICI monotherapy may not need treatment interruption or discontinuation.